Role of the ubiquitin–proteasome system in brain ischemia: Friend or foe? - Caldeira, Margarida V. (2014)
The ubiquitin–proteasome system (UPS) is a catalytic machinery that targets numerous cellular proteins for degradation, thus being essential to control a wide range of basic cellular processes and cell survival. Degradation of intracellular proteins via the UPS is a tightly regulated process initiated by tagging a target protein with a specific ubiquitin chain. Neurons are particularly vulnerable to any change in protein composition, and therefore the UPS is a key regulator of neuronal physiology. Alterations in UPS activity may induce pathological responses, ultimately leading to neuronal cell death. Brain ischemia triggers a complex series of biochemical and molecular mechanisms, such as an inflammatory response, an exacerbated production of misfolded and oxidized proteins, due to oxidative stress, and the breakdown of cellular integrity mainly mediated by excitotoxic glutamatergic signaling. Brain ischemia also damages protein degradation pathways which, together with the overproduction of damaged proteins and consequent upregulation of ubiquitin-conjugated proteins, contribute to the accumulation of ubiquitincontaining proteinaceous deposits. Despite recent advances, the factors leading to deposition of such aggregates after cerebral ischemic injury remain poorly understood. This review discusses the current knowledge on the role of the UPS in brain function and the molecular mechanisms contributing to UPS dysfunction in brain ischemia with consequent accumulation of ubiquitin-containing proteins. Chemical inhibitors of the proteasome and small molecule inhibitors of deubiquitinating enzymes, which promote the degradation of proteins by the proteasome, were both shown to provide neuroprotection in brain ischemia, and this apparent contradiction is also discussed in this review.